The influence of the metabolic activity of the intestinal microflora on the severity and duration of rotavirus diarrhea in early-aged children - N. V. Vorobiova; O. V. Usachova; Ye. A. Silina; O. O. Furyk (Zaporozhye State Medical University, 2023)
The aim is to determine the pathogenetic role of the metabolic activity of the intestinal microflora in the formation of the severity and duration of rotavirus diarrhea in early-aged children. Materials and methods. 60 children aged 1-24 months with RVI were included in the research group. The metabolic activity of the intestinal microflora was determined by detecting short-chain fatty acids (SCFAs) in feces in the dynamics of the disease (the absolute concentration (μmol/l) of acetate, propionate, butyrate, the total concentration of SCFAs and the value of the anaerobic index (AI) on the 3rd, 5th and 10th days of RVI) using high-performance liquid chromatography with LC-MS chromatography Agilent 1260 Infinity HPLC System, USA. Results. From the 5th day of RVI, with a minimally expressed diarrheal syndrome, a higher total pool of SCFA and higher AI values were observed than with moderate-severe and severe diarrhea (p ˂ 0.05 on the 5th and 10th days of RVI). A longer duration of the diarrheal syndrome in children was associated with a decrease in the metabolic activity of sucrolytic intestinal bacteria: patients with diarrhea ≤5 days had 2.4 times higher indicators of the total pool of SCFA, than patients with the duration of diarrhea ≥6 days (p ˂ 0.05). The degree of reduction in the concentration of C3 and the value of AI on the 2-3rd days of RVI was directly correlated with the duration of diarrhea, which increased by 1 day with a decrease in C3 by 20.6 μmol/l or a decrease in AI by 0.05. Conclusions. The influence of the intestinal microflora metabolic deficiency on the severity of diarrhea in early-aged children manifests itself from the 5th day of illness. A decrease in the concentration of propionate and the value of AI on the 2-3rd days of the disease is the earliest indicator of prolonged diarrhea in children with RVI.